Efektivitas Pengendalian Internal Dalam Mencegah Fraud Guna Mendukung Terwujudnya GCG Pada Perumda Air Minum Mual Nauli Tapteng - Tigor Panuturi Tambunan; Masril Tua Rambe; Deliana Deliana; Ilham Napitupulu (Mahesa Research Center, 2024)
The internal control system at Perumda Mual Tapteng Regency is implemented to find out whether the management system has been implemented well or not and to avoid cost leaks. What this research aims to achieve is to analyze the effectiveness of implementing an internal control system as an effort to control or even prevent incidents of fraud. Qualitative methods were applied in this research using data collection techniques carried out through observation and interviews (in depth interviews). The results of this research indicate that Perumda Mual Nauli, Central Tapanuli Regency has succeeded in implementing an effective internal control system.